Exergy analysis of diesel/biodiesel combustion in a homogenous charge compression ignition (HCCI) engine using three-dimensional model. (December 2016) - Jafarmadar, Samad; Nemati, Peyman
Abstract: Exergy analysis gives the presentation of a system relative to its best performance. In addition, the exergy destructed can react with its surrounding and harm environment processes. This study investigated the effect of biodiesel fuel blended with diesel fuel (i.e. 0%, 20%, and 50% blending of biodiesel fuel with conventional diesel fuel) on various exergy terms in an HCCI engine. To model the energy balance a 3-D CFD code was utilized. Using energy and combustion analyses results, the researchers calculated various exergy terms by developing a FORTRAN based code. To ensure the integrity of modeling, the results of the in-cylinder pressure and heat release rate were compared with the experimental results for pure diesel fuel. This comparison indicated a good agreement between the two. With crank position at three fuel compositions, different rates of exergy and cumulative exergy terms were identified and calculated separately. With the increase in the biodiesel volume percentage from 0% to 20% and 50%, exergy efficiency increased by 4.9% and 5.7%. Also, the cumulative heat loss exergy decreased by 4.4% and 9.7%, respectively. Highlights: When biodiesel quantity increased from B0 to B50: The exergy efficiency increases by 6.65%. The irreversibility increases by 1.28%. The cumulative heat loss exergy increases by 1.28%. The exhaust total exergy increases by 7.72%.